1976
DOI: 10.1002/1097-4679(197607)32:3<687::aid-jclp2270320343>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Client involvement in goal setting and its relationship to therapeutic outcome

Abstract: PROBLEMGoal attainment scaling was introduced to mental health programs for the purpose of treatment evaluation(a). It also has been suggested that goal attainment scaling should be incorporated in the clinical record for the purpose of treatment planning@). Finally, it has been suggested that if the client and therapist conjointly establish goals and specify outcome levels, then goal attainment scaling becomes a form of therapeutic contract (*). The present study explores the relationship between patient invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 1 publication
1
12
0
1
Order By: Relevance
“…The majority of the small number of providers who responded to the online survey indicated that the experience of working with clients with the GAS approach was at least as good as or better than past practice. This finding reflects the claims in the literature that the process of GAS is a useful mechanism for supporting comprehensive planning, for setting clear expectations of all parties involved in the plan (i.e., client, health care providers, rehabilitation providers), and for facilitating discussions between clients and providers (10)(11)(12). Where issues were raised in relation to the GAS procedure, these related primarily to matters that could be addressed by providing ongoing training and resources, particularly when new providers start to use GAS.…”
Section: Discussionsupporting
confidence: 78%
“…The majority of the small number of providers who responded to the online survey indicated that the experience of working with clients with the GAS approach was at least as good as or better than past practice. This finding reflects the claims in the literature that the process of GAS is a useful mechanism for supporting comprehensive planning, for setting clear expectations of all parties involved in the plan (i.e., client, health care providers, rehabilitation providers), and for facilitating discussions between clients and providers (10)(11)(12). Where issues were raised in relation to the GAS procedure, these related primarily to matters that could be addressed by providing ongoing training and resources, particularly when new providers start to use GAS.…”
Section: Discussionsupporting
confidence: 78%
“…5,6 Positive investigations regarding patient involvement in goal setting have shown an increase in patient adherence, 7 goal attainment and satisfaction. 8 Further positive results have facilitated greater physical gains 9,10 and increased patient control in managing the consequences of injury. 11 In the area of spinal cord injury research, such patient involvement is known to enhance and extend physical, social and psychological adjustments following discharge from the acute management setting.…”
Section: Introductionmentioning
confidence: 99%
“…In practice and in intervention research, autonomous motivation can be fostered by allowing patients, either individually or in collaboration with practitioners, to set their own goals for treatment (18). Goals set in a collaborative manner have been shown to increase patient adherence to rehabilitation goals (19) and to increase achievement of goals (20). In other populations, autonomous motivation has been linked to adherence to both physical activity and medication regimens (21, 22), both of which can improve reports of pain (23, 24) and QOL (23, 25) among patients with RA.…”
Section: Introductionmentioning
confidence: 99%